Pengaruh Kualitas Produk dan Citra Merek terhadap Keputusan Pembelian Skin Care Ms Glow - Ismi, Nurul; Iriani, Iriani; Syafrizal, Syafrizal (Universitas Islam Islam Sumatera Utara, 2023)
The purpose of this research is to determine the influence of product quality and brand image on the purchasing decisions of Ms Glow skincare products at the Faculty of Economics and Business, Islamic University of North Sumatra. This type of research is associative with a sample of 62 students from the 2020 Management Study Program at the Faculty of Economics and Business, Islamic University of North Sumatra, using multiple linear regression analysis. The results of this study indicate that product quality has a positive and significant influence on the purchasing decisions of Ms Glow skincare products at the Faculty of Economics and Business, Islamic University of North Sumatra. Brand image also has a positive and significant influence on the purchasing decisions of Ms Glow skincare products at the Faculty of Economics and Business, Islamic University of North Sumatra. Both product quality and brand image have a positive and significant influence on the purchasing decisions of Ms Glow skincare products at the Faculty of Economics and Business, Islamic University of North Sumatra